Extraordinary appeals of the European Commissioner of Human Rights in the Light of Judgement of the ECtHR Wałęsa v. Poland - Piekarczyk, Sławomir; Wentkowska, Aleksandra (PRAWO i WIĘŹ, 2024)
The institution of extraordinary appeal, provided by Polish law, was the subject of a multi-faceted assessment by The European Court of Human Rights in the case of Wałęsa v. Poland. In its judgment, the Court found its procedure inconsistent with the standards of a fair trial and the principle of legal certainty due to several defects identified in the judgment. The article compares the relevant statements in the mentioned judgment with the practice of filing extraordinary appeals by the Polish Commissioner for Human Rights (Ombudsman). To fulfill this task, the authors conducted a qualitative and quantitative analysis of all extraordinary appeals filed by the Ombudsman from the inception of the institution until the end of 2023. The research findings indicate that the body in question does not utilize the extraordinary appeal mechanism in a instrumental manner. Its actions are guided by the objective underlying its introduction by the legislator, to eliminate valid judgments that are grossly unjust and unlawful from circulation.